Freeze-drying of HI-6-loaded recombinant human serum albumin nanoparticles for improved storage stability - Dadparvar, Miriam; Wagner, Sylvia; Wien, Sascha; Worek, Franz; von Briesen, Hagen; Kreuter, Jörg (European journal of pharmaceutics and biopharmaceutics, 2014)
•HI-6 can be stabilised by binding to nanoparticles and lyophilisation.•Trehalose- and sucrose-containing formulations were superior to mannitol.•Nanoparticles enabled HI-6 transport over a porcine endothelial cell model. Severe intoxications with organophosphates require the immediate administration of atropine in combination with acetyl cholinesterase (AChE) reactivators such as HI-6. Although this therapy regimen enables the treatment of peripheral symptoms, the blood–brain barrier (BBB) restricts the access of the hydrophilic antidotes to the central nervous system which could lead to a fatal respiratory arrest. Therefore, HI-6-loaded albumin nanoparticles were previously developed to enhance the transport across this barrier and were able to reactivate organophosphate-(OP)-inhibited AChE in an in vitro BBB model. Since HI-6 is known to be moisture-sensitive, the feasibility of freeze-drying of the HI-6-loaded nanoparticles was investigated in the present study using different cryo- and lyoprotectants at different concentrations. Trehalose and sucrose (3%, w/v)-containing formulations were superior to mannitol concerning the physicochemical parameters of the nanoparticles whereas trehalose-containing samples were subject of a prolonged storage stability study at temperatures between −20°C and +40°C for predetermined time intervals. Shelf-life computations of the freeze-dried HI-6 nanoparticle formulations revealed a shelf-life time of 18months when stored at −20°C. The formulations’ efficacy was proven in vitro by reactivation of OP-inhibited AChE after transport over a porcine brain capillary endothelial cell layer model.